Transport Test of Total Flavonoid Model of Strawberry Emulgel (Fragaria vesca L.) Through Shed Snakeskin Membrane - Dian Eka Ermawati; Suwaldi Martodiharjo; T.N Saifullah Sulaiman (Majalah Farmaseutik, 2023)
Strawberries contain antioxidants, including quercetin-3-β-D-glucoside, coenzyme Q10, anthocyanins pelargonidin-3-O-glucoside, and cyanidin-3-glucoside. The amount of anthocyanins and flavonoids in fruit tends to decrease by 40-50% after the formulation process, so it is necessary to develop a formula to be applied as a topical preparation. The combination of emulsifiers can stabilize the active substance and increase the permeation of the preparation. This study aims to determine the total flavonoid permeation profile of strawberry fruit emulgel preparations with a combination of emulsifiers. This study used a total flavonoid model from strawberry emulgel. Emulgel was prepared with a combination of emulsifier span 80: croduret 50: propylene glycol at a ratio of 2: 4: 2. The permeation test was carried out using a modified vertical Franz diffusion cell equipped with Shed Snakeskin membrane. The permeation test results showed that the cumulative amount of total flavonoids transported across the shed snakeskin membrane was 117.14 g/cm2 out of a total of 2.24 mg of strawberries in the emulgel formula for 5 hours. The permeability of the snakeskin shed membrane was 2.84x10-5 g/cm2, and the flux value was 6.6x10-5 g/sec. The release kinetics follow the Higuchi kinetic model with the diffusion mechanism.